(untitled) (Foro de Educacion, 2016)
Education for Citizenship was an educational area implanted in the Spanish educational system with the Organic Law of Education (LOE), of 2006, under the Socialist government of Jose Luis Rodriguez Zapatero. From the moment that the Government expressed its intention to develop this type of civic and democratic education, responding to various responsibilities and commitments with the United Nations and the Council of Europe, theocons sectors of Spanish society mobilized to delegitimize, obstruct and eliminate the implementation of this education. The People’s Party was very active in this mobilizer process against Education for Citizenship. The intention of this article is to examine the discursive line and of action followed by the People’s Party in relation to this education. The analysis will verify how the action of the People’s Party to eliminate this educational area, materialized with the gradual implementation of the new Organic Law of Education Quality Improvement (LOMCE), of 2013, has supported the discourse of Catholic neotraditionalism and has placed to Spain at the tail end of the other European countries in civic and democratic education, generating the criticism from the international community in this regard.